South African eucalypts: Health, trees, and atmospheres in the colonial contact zone. (November 2016) - Flikke, Rune
Highlights: Smell was an important factor in colonial landscape alterations in South Africa. Early transfers of eucalypts to South Africa are accounted for through olfaction. Eucalypt transfers uncover the significance of atmosphere in the colonial conquest. Abstract: In this article I suggest that a reading of previous studies, which cast the early transfers of eucalyptus to South Africa along economic and aesthetic rationales can be enhanced by medical history. Through a case from King William's Town in the 1870s, I show that the appeal of the eucalyptus hinged on the olfactory aspect of the trees, which were conceived as an important public health factor. I then proceed to outline how a clearer understanding of the role of olfaction in ecological studies can uncover new aspects of social dynamics and human relations to the natural environment. I argue that taking the atmosphere seriously as the medium through which we interact with the world, opens for an understanding of olfaction as an important and largely unexplored ethos that guided the dramatic reshaping of the colonial landscapes during much of the nineteenth century.